THE EFFECT OF RISK PERCEPTION AND CUSTOMER EXPERIENCE ON GOPAY PURCHASE INTENTION IN THE MILLENIAL GEN - Prinshi Rabbiatul Adzawiah; Herning Indriastuti (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2023)
This research aims to examine how perceived risk and customer experience influence the repurchase intention of the millennial generation of GOPAY users. The independent variables in this research are perceived risk and customer experience, while the dependent variable is repurchasing intention. This research was conducted on the millennial generation of GOPAY users consisting of 130 respondents. This research is quantitative. Data collection using a questionnaire by testing the perceived risk and customer experience on repurchase interest. Data analysis using PLS (Partial Least Square) analysis technique. The results of this research show that risk perception has a positive and significant effect on the repurchase interest of the millennial generation of GOPAY users and customer experience has a positive and significant effect on the repurchase interest of the millennial generation of GOPAY users.